College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.4 - Average Rate of Change of a Function - 2.4 Exercises - Page 224: 15


(a) 51 (b) 17

Work Step by Step

We are given: $h(t)=2t^2-t$; $t=3$, $t=6$ (a) We calculate the net change: $h(6)-h(3)=[2(6)^{2}-6]-[2(3)^{2}-3]=(2*36-6)-(2*9-3)=66-15=51$ (b) We calculate the average rate of change: $\displaystyle \frac{h(6)-h(3)}{6-3}=\frac{51}{3}=17$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.